Bioensayo para la detección de PHYTOPHTHORA CINNAMOMI EN EL SUELO DE RODALES AFECTADOS POR LA SECA DE QUERCUS (III Congreso Forestal Español, 2001)
The isolation of Phytophthora spp. from soil samples is often difficult, even using indirect methods which combine baiting techniques and selective media. Apple or avocado fruits or carnation petals are some of the most common baits used for the isolation of P. cinnamomi from infested soils where Quercus ilex and Q. suber have been affected by root rot and decline. However, the use of these baits has serious limitations because of the contamination by several fungi and bacteria. The aim of this work was to improve the baiting technique for the pathosystem P. cinnamomi / Quercus spp. The effect of different factors, including several baits (leaves, fruits, cotyledons, radicles), the soil:water dilution, and the incubation time, was checked using a soil mixture artificially infested with several isolates of P. cinnamomi. The most effective baiting method included baits of eucalyptus phyllodium pieces (Eucalyptus globulus and less effective E. camaldulensis), 1:6 soil:water relation, and 4 days incubation period. The efficiency of this method has been tested for the detection of P. cinnamomi in naturally infested soil samples from fields where the root rot caused by this pathogen had been previously diagnosed